Molecular modulation of human α7 Nicotinic Receptor by amyloid-β peptides - Lasala, Matías Marcelo (2018)
myloid β peptide (Aβ) is a key player in the development of Alzheimer disease (AD). It is the primary component of senile plaques in AD patients and is also found in soluble forms. Cholinergic activity mediated by α7 nicotinic receptors has been shown to be affected by Aβ soluble forms. To shed light into the molecular mechanism of this effect, we explored the direct actions of oligomeric Aβ1-40 and Aβ1-42 on human α7 by fluorescence spectroscopy and single-channel recordings. Fluorescence measurements using the conformational sensitive probe crystal violet (CrV), which shows different affinities for resting and desensitized states, revealed that Aβ induces α7 concentration-dependent conformational changes. At 100 pM, Aβ displaces CrV Kd value for the resting state towards that of the desensitized state from which α7 is still reactive to carbamycholine (Carb). These observations are compatible with the induction of active/desensitized states as well as of a novel conformational state in the presence of both Aβ and Carb. At 100 nM Aβ, α7 adopts a resting-state-like structure which does not respond to Carb, indicating the stabilization of α7 in a blocked state. In real time, we found that Aβ is capable of eliciting α7 channel activity either in the absence or presence of the positive allosteric modulator PNU-120596. Activation by Aβ is favored at picomolar or low nanomolar concentrations and is not detected at micromolar concentrations. At high Aβ concentrations, the durations of the activation episodes elicited by ACh are significantly reduced, an effect compatible with slow open- channel block. We conclude that Aβ directly affects α7 function and acts as an agonist and a negative modulator: activation of α7 by low Aβ concentrations may be involved in beneficial physiological effects, and the reduced α7 activity in the presence of higher Aβ concentrations may contribute to the cholinergic signaling deficit and may be involved in the initiation and development of AD